Correctional and forensic mental health services in Bangladesh - Khan, Al Aditya (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
Bangladesh is a lower-middle-income country in Southern Asia with the highest population density in the world. The prison population is large in absolute terms, although incarceration rates are relatively low. Prisons are overcrowded, with a high proportion of remandees, many of whom wait years for trial. There is no probation service, and community sentences do not exist. Bangladesh has few mental health professionals to meet the mental health needs of people in custody. Forensic mental health services are not well developed and there are no formal prison mental health services for people in prison. Mechanisms exist to transfer prisoners with mental illness to hospitals for treatment but these tend to be used only for the most unwell people and there is little community aftercare. Bangladesh is a signatory to several international human rights agreements that promote rehabilitation for people in custody, but in reality, these principles are not fully upheld. The general public and government frequently prioritise public protection and punishment. The stigma and social consequences accompanying criminal conviction remain high. Despite these challenges, there have been several successful recent initiatives to introduce rehabilitative programmes for people who have offended. These have included occupational skills training, income generation schemes and educational programmes. Furthermore, there is important legislative change underway, including the recent Mental Health Act, proposed changes to the Prison Act and the government declaring prisons “correction centres”. These actions could increase the emphasis on rehabilitation.